A Conceptual Framework for Understanding Variability in Student Perceptions - Gencoglu, Bilge; Helms-Lorenz, Michelle; Maulana, Ridwan; Jansen, Ellen P. W. A. (Frontiers in Psychology, 2021)
Student perceptions using surveys are frequently used to measure student perceptions of teachers’ teaching quality in secondary and higher education. Research shows that the variance in student perceptions exists within a class as well as between countries. However, the influence of individual and cultural level factors on the variance of student perceptions is less well studied. More insights are needed to understand the mechanisms underlying the variance in student perceptions in-depth. Insights into determinants of student perceptions of teaching quality could become valuable towards understanding school-related outcomes. A conceptual framework is put forward in this study to enhance our understanding of manifestations of student perceptions of teaching quality. It is suggested that value orientations at the individual and cultural level as well as social desirability may play a role in understanding student perceptions of teaching quality. Understanding students’ individual and collective perceptions of teaching quality can contribute to teachers’ sense-making of their student evaluations. It is argued that this understanding could contribute to enhancing the development of teaching quality and ultimately education quality.